Design and Additive Construction of a Video-Laryngoscope for Endotracheal Intubation of Adult Patients - Matehuala-Morán, Iván; Pino Pérez, Axel Yael; Fuentes-Alvarez, Ruben; Beltrán Fernández, Juan Alfonso; Hernandez-Gilsoul, Thierry; Saldaña Villaseñor, Pedro Alejandro; Rojas-Vega, Lorena; Ramírez Cadena, Miguel de Jesús; Alfaro-Ponce, Mariel (Frontiers in Materials, 2022)
As a result of the pandemic, cases requiring endotracheal intubation have increased to support breathing through mechanical ventilation; this procedure is necessary when a patient cannot breathe on their own due to respiratory failure, for it, the laryngoscope is employed. Even when employing a laryngoscope is possible to injure the patient due to poor visibility at intubation. As a solution, some video-laryngoscopes present many advantages, such as reducing injuries, lowering the number of attempts to secure the airway and the image's quality, and the easy recognition of the laryngeal structures. However, this type of device is not accessible for many health institutions due to the price. Therefore, this paper proposes the design of a video-laryngoscope in a Computer-Aided-Design (CAD) software and constructed by additive manufacturing. For this design, the identification of the needs of the medical personnel in the Anesthesiology and Emergency Medicine Departments from the Instituto Nacional de Ciencias Médicas y Nutrición Salvador Zubirán (INCMNSZ) were taken into account. The design specifications provided by the users were used to create a proposal solution at the conceptual design level. The material and camera for the prototype instrumentation are presented with the model's geometric parameters. Subsequently, the virtual modeling of the device was carried out, and rapid prototypes were built to validate the performance of the design proposal. The final device was constructed by Selective Laser Sintering (SLS) using Nylon 12 as a construction material. Finally, the device was evaluated using airway simulators with the support of medical specialists to determine its functionality.